Transforming MRCPsych theory examinations: digitisation and very short answer questions (VSAQs). (February 2022) - Scheeres, Karl; Agrawal, Niruj; Ewen, Stephanie; Hall, Ian
Abstract : Many examinations are now delivered online using digital formats, the migration to which has been accelerated by the COVID-19 pandemic. The MRCPsych theory examinations have been delivered in this way since Autumn 2020. The multiple choice question formats currently in use are highly reliable, but other formats enabled by the digital platform, such as very short answer questions (VSAQs), may promote deeper learning. Trainees often ask for a focus on core knowledge, and the absence of cueing with VSAQs could help achieve this. This paper describes the background and evidence base for VSAQs, and how they might be introduced. Any new question formats would be thoroughly piloted before appearing in the examinations and are likely to have a phased introduction alongside existing formats.